Foundation engineering analysis and design - Huang, An-Bin; Yu, Hai-Sui (CRC Press, Taylor & Francis Group, 2018)
One of the core roles of a practising geotechnical engineer is to analyse and design foundations. This textbook for advanced undergraduates and graduate students covers the analysis, design and construction of shallow and deep foundations and retaining structures as well as the stability analysis and mitigation of slopes. It progressively introduces critical state soil mechanics and plasticity theories such as plastic limit analysis and cavity expansion theories before leading into the theories of foundation, lateral earth pressure and slope stability analysis.